Forming Data on the Losses in a Business Entity Accounting with the Purpose of Ensuring its Economic Security - E. G. Tokmakova; Yu. A. Yukhtanova; D. L. Skipin (Учёт. Анализ. Аудит)
Ensuring the economic security of an economic entity, as a state of its protection from the threats to sustainable development, is an important component of business in modern conditions. Losses, when viewed through the lens of the economic security — are expenses that occur in the present and are caused by certain factors that can be eliminated or prevented. Thus, in the future, excluding losses means protecting businesses from the threats of unreasonable expenses that slow down economic development. The article is devoted to the formation of information about the losses of an economic entity in accounting. The research methodology is based on a conceptual understanding of business losses, judging from the need to ensure its economic security and accounting capabilities. Basing on the analysis of the accounting financial statements of oil and gas companies, it was concluded that there is no available information about expenses that qualify as the losses of the company. The result of the study is the presented accounting method which is based on singling out the losses as a separate object of accounting. The proposed method, when applied in practice, will allow the economic security service of an economic entity, which has full information about the losses provided by the accounting department, to develop measures to minimize losses or prevent them.